Conversion table and specification for Contrast Sensitivity (CS) function between Pelli-Robson chart (long unit) and M&S Smart System II (%) - Hilmi, Mohd Radzi; Che Azemin, Mohd Zulfaezal; Mohd Tamrin, Mohd Izzuddin; Mohd. Kamal, Khairidzan (2021)
This work provides the conversion between log scale to percentage in form of a table of conversion between Pelli Robson and M&S Smart System II to assist clinicians in measuring and analysing CS function between these two instruments.